Preparation and characterization of conducting polyaniline layered magnetic nano composite polymer particles. (22nd May 2013) - Ahmad, H.; Kumar, K.; Rahman, M. A.; Rahman, M. M.; Miah, M. A. J.; Minami, H.; Nuri, M. A.
Abstract : Considering the application potentials of organic materials possessing both conducting and ferromagnetic functions in various electronic devices, an attempt was made to prepare conducting polyaniline (PANI) layered magnetic nano composite polymer particles. Two routes were used to modify magnetic Fe3 O4 core particles. In one route, seeded emulsion polymerization of methyl methacrylate (MMA) was carried out in presence of nano‐sized Fe3 O4 core particles. In another route, cross‐linker ethyleneglycol dimethacrylate (EGDM) was used in addition to MMA. The modified composite particles were named as Fe3 O4 /PMMA and Fe3 O4 /P(MMA‐EGDM), respectively. Finally, seeded chemical oxidative polymerization of aniline was carried out in the presence of Fe3 O4 /PMMA and Fe3 O4 /P(MMA‐EGDM) composite seed particles to obtain Fe3 O4 /PMMA/PANI and Fe3 O4 /P(MMA‐EGDM)/PANI composite polymer particles. The modification of Fe3 O4 core particles was confirmed by electron micrographs, FTIR, UV–visible spectra, X‐ray photoelectron spectra, X‐ray diffraction pattern and thermogravimetric analyses. A comparative study showed that crosslinking of intermediate shell improved the magnetic susceptibility and electrical conductivity of PANI layered magnetic nano composite particles. Copyright © 2013 John Wiley & Sons, Ltd.